2015
DOI: 10.1111/obr.12256
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate transporters: new players in body weight regulation

Abstract: Over the last two decades, several genes have been identified that appear to play a role in the regulation of energy homeostasis and body weight. For a small subset of them, a reduction or an absence of expression confers a resistance to the development of obesity. Recently, a knockin mouse for a member of the monocarboxylate transporter (MCT) family, MCT1, was demonstrated to exhibit a typical phenotype of resistance to diet-induced obesity and a protection from its associated metabolic perturbations. Such fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 110 publications
2
52
0
1
Order By: Relevance
“…Monocarboxylates that include short-chain fatty acids and ketone bodies have been shown to undergo some alterations during obesity development (4,22,23,43). However, mecha- nisms by which they could be implicated in the pathophysiology of obesity have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Monocarboxylates that include short-chain fatty acids and ketone bodies have been shown to undergo some alterations during obesity development (4,22,23,43). However, mecha- nisms by which they could be implicated in the pathophysiology of obesity have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, they can act as fuel sensors impacting food intake and body weight. Altered MCT expression levels in key tissues in response to metabolic status, especially in the brain, muscles, liver, intestine, pancreas, and adipose tissue are suggested to be important determinants with respect to whole body energy balance 48. As comprehensively reviewed by Carneiro et al ., 48 considerable alterations in MCT1, MCT2, or MCT4 expression in these tissues are found in accordance to metabolic states (e.g., in obese or fasting subjects).…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Although, again, most studies refer to rodent or in vitro models, alterations were also confirmed in human tissues. For instance, MCT4 was found to be overexpressed in muscle of obese subjects but decreased after weight loss 48. Most striking results were achieved using a heterozygous transgenic MCT1 knockout mouse model (MCT1 +/− ; MCT1 −/− homozygote knockout is lethal), which has been demonstrated to be resistant to diet‐induced obesity 49.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Indeed, several MCT isoforms and their substrates are known to modulate various components of weight homeostasis, ranging from their central effects on food intake to peripheral effects in the browning of white adipose tissue . In reviewing the role of MCTs as new players in weight homeostasis, Carneiro and Pellerin point out that the proof of concept about the potentially critical role of MCT in weight regulation has recently been demonstrated in the ability of haploinsufficient MCT1 mice to resist obesity when exposed to an obesogenic diet – by reducing food intake and intestinal nutrient absorption, as well as increasing resting metabolic rate. Furthermore, they emphasized that the expression of cerebral MCT isoforms can be modulated by alterations of peripheral metabolism and that considering their distribution and their suggested functions in various aspects of metabolism, it is likely that their expression both in the central nervous system and in the periphery might be influenced by nutritional manipulations including caloric restriction and refeeding.…”
Section: Nutrient Transporters: New Players In Weight Regulationmentioning
confidence: 99%